2008
DOI: 10.1007/s10585-008-9171-5
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity of neoplastic ovarian epithelium: unique cadherin profiles in tumor progression

Abstract: The mesodermally derived normal ovarian surface epithelium (OSE) displays both epithelial and mesenchymal characteristics and exhibits remarkable phenotypic plasticity during post-ovulatory repair. The majority of epithelial ovarian carcinomas (EOC) are derived from the OSE and represent the most lethal of all gynecological malignancies, as most patients (~70%) present at diagnosis with disseminated intra-abdominal metastasis. The predominant pattern of EOC metastasis involves pelvic dissemination rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
172
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(183 citation statements)
references
References 96 publications
(154 reference statements)
10
172
1
Order By: Relevance
“…Modulation of cell-cell and cell-matrix adhesion are key events in ovarian cancer metastasis, as intraperitoneal adhesion of malignant cells and multicellular aggregates combined with localized integrin-mediated invasion of the collagen-rich submesothelial matrix are necessary to anchor secondary lesions (5,40). Intraperitoneal ovarian cancer metastasis is mediated by adhesion via integrins ␣2␤1 and ␣3␤1 to peritoneal mesothelial cells displaying surface expression of collagen and the exposed interstitial (types I and III) collagen-rich submesothelial matrix, and antibodies directed against these integrins block collagen binding (41)(42)(43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modulation of cell-cell and cell-matrix adhesion are key events in ovarian cancer metastasis, as intraperitoneal adhesion of malignant cells and multicellular aggregates combined with localized integrin-mediated invasion of the collagen-rich submesothelial matrix are necessary to anchor secondary lesions (5,40). Intraperitoneal ovarian cancer metastasis is mediated by adhesion via integrins ␣2␤1 and ␣3␤1 to peritoneal mesothelial cells displaying surface expression of collagen and the exposed interstitial (types I and III) collagen-rich submesothelial matrix, and antibodies directed against these integrins block collagen binding (41)(42)(43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to enzymes and enzyme receptors, expression of two genes commonly associated with EMT, vimentin and snail, was also induced by integrin clustering. Ovarian cancers typically display both epithelial and mesenchymal characteristics, and the mesenchymal marker vimentin is widely expressed in tumor specimens (5). Snail is a key inducer of EMT and functions as a negative regulator of E-cadherin transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Tumor cells show evidence of phenotypic plasticity that is adaptive from the point of view of the tumor, in terms of processes such as tumor growth, survival and metastasis (Yacoby, 2005;Hudson et al, 2008). The molecular basis of tumor plasticity remains poorly understood, although presumably it makes use of mechanisms that have a role in normal development (Feinberg, 2007).…”
Section: The Prm Modelmentioning
confidence: 99%
“…E-cadherin is a cell adhesion protein, which plays a major role in maintaining intercellular junction in epithelial tissue (Davies et al, 1998;Landen et al, 2008). E-cadherin is uniformly expressed in ovarian inclusion cysts, benign ovarian cancers and ovarian cancer (Imai et al, 2004;Hudson et al, 2008). We found that E-cadherin was significantly upregulated after treatment with 5μM DZNep for 48 h.…”
Section: Discussionmentioning
confidence: 74%